2016
DOI: 10.1186/s12879-016-1528-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors effecting influenza vaccination uptake among health care workers: a multi-center cross-sectional study

Abstract: BackgroundThe present study aimed to identify factors affecting vaccination against influenza among health professionals.MethodsWe used a multi-centre cross-sectional design to conduct an online self-administered questionnaire with physicians and nurses at state and foundation university hospitals in the south-east of Turkey, between 1 January 2015 and 1 February 2015. The five participating hospitals provided staff email address lists filtered for physicians and nurses. The questionnaire comprised multiple ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 33 publications
6
52
2
Order By: Relevance
“…This finding supports us in preparing special programs suitable for different occupational categories in order to increase vaccine coverage [19]. In the study reported from Turkey, found the rate of regular vaccination to be 15.2% in the doctor group and reported that the rate of vaccination was low especially among the nurses who are regularly vaccinated [8]. In a study by Wong et al reported the vaccination rate as 38% among clinical nurses [20].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This finding supports us in preparing special programs suitable for different occupational categories in order to increase vaccine coverage [19]. In the study reported from Turkey, found the rate of regular vaccination to be 15.2% in the doctor group and reported that the rate of vaccination was low especially among the nurses who are regularly vaccinated [8]. In a study by Wong et al reported the vaccination rate as 38% among clinical nurses [20].…”
Section: Discussionsupporting
confidence: 55%
“…In the USA, influenza vaccination rates reached 75.2% in 2013-14 season due to the determination of influenza vaccine coverage as a performance criterion and mandatory vaccination policies, while this rate is still around 30% in Europe [5]. Although free influenza vaccination has been provided to healthcare workers in Turkey since 2002, vaccination rates are not yet at the desired level [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This signifies a need to target nurses with awareness and educational campaigns incorporating the concepts of protecting one's family from influenza during a pandemic situation. Also, studies demonstrated that side effects and perceived ineffectiveness of the influenza vaccine were factors contributing to HCP vaccination behaviours (Asma et al, 2016;Naleway et al, 2014;Nutman & Yoeli, 2016 Moreover, increasing influenza vaccine coverage may be crucial for implementing effective policies, such as a mandatory immunisation program for nurses (Haridi et al, 2017;Jaiyeoba et al, 2014;Winston et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We found in all 3 seasons that other HCWs appeared to have higher IV uptake compared to nurses and physicians. Although we included HCWs, many previous studies limited their analyses to physicians and nurses and ignored other HCWs (25). Speculation about why HCWs appeared to have high IV uptake compared to nurses and physicians is not straightforward and needs to consider a wide range of demographic, educational, occupational, socioeconomic and health confounders, as well as residual confounding due to IV knowledge, attitudes and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Speculation about why HCWs appeared to have high IV uptake compared to nurses and physicians is not straightforward and needs to consider a wide range of demographic, educational, occupational, socioeconomic and health confounders, as well as residual confounding due to IV knowledge, attitudes and practice. Such confounders include age, sex, marital status, education level, specialization, years of service, chronic comorbidity (e.g., those with diabetes or cardiovascular diseases were more likely to be vaccinated against seasonal influenza (25)), as well as personal beliefs about vaccine safety and efficacy. Indeed, research has highlighted a prevalent individual approach to vaccination among HCWs, as well as ethical issues concerning physicians who seem not to be concerned about the impact of influenza on themselves or their patients (25).…”
Section: Discussionmentioning
confidence: 99%